(untitled) (Texas Journal of Philology, Culture and History, 2024)
This research discusses the points that Imam Mohammed Al-Ebyari corrected scientists misbelieves who explained Al-Durra Al-Modeyya for Imam lbn Al-Jazari , then the comments that relates to validity using scientists marbles as a reference which the researcher depended on